Psychotropic drugs and CYP2D6 in late-life psychiatric and neurological disorders. What do we know?. Issue 12 (2nd December 2017) - Seripa, Davide; Lozupone, Madia; Stella, Eleonora; Paroni, Giulia; Bisceglia, Paola; La Montagna, Maddalena; D'onofrio, Grazia; Gravina, Carolina; Urbano, Maria; Priore, Maria Giovanna; Lamanna, Angela; Daniele, Antonio; et al.
ABSTRACT: Introduction : Late-life psychiatric and neurological disorders (LLPND) are interesting models to understand the potential role of pharmacogenetics in drug management, since several pharmacological approaches for treating LLPND have proven to be ineffective or deleterious, thus resulting in therapeutic failures (TF) and adverse drug reactions (ADR). Common variants in the genes encoding the cytochrome P450 (CYP) enzyme system, the 'engine room' of drug metabolism, together with well-known age-related increased polypharmacy also contributed to the prevalence of TF and ADR observed in these patients, also rising number and time of hospital readmissions and rate of institutionalizations. Areas covered : The genetics of CYP and how it may be used for the management of the outcomes of the most frequent drugs (antidepressants, antipsychotics, anticholinesterase inhibitors, and anxiolytics) used in LLPND. Expert opinion : Tailored CYP-based pharmacological treatments of LLPND will reduce TFs and ADRs, improving patient's life, reducing number and dosage of administered drugs, and the number and duration of hospital readmissions, saving costs for clinical management of LLPND. Pharmacokinetic interactions are less predictable than pharmacodynamic ones and several requests are made to regulatory organisms for the pharmacological management of frail older patients affected by LLPND.